Identification of small interfering RNA targeting Signal Transducer and Activator of Transcription 6: Characterisation and selection of candidates for pre-clinical development - Healey, G; Zinnen, S; Lockridge, J; Richard, I; Evans, N; Walker, W (Library Publishing Media, 2010)
The interleukin (IL)-13 pathway and its associated transcription factor, signal transducer and activator of transcription 6 (STAT6), have been clearly implicated in the pathogenesis of bronchial asthma. We have developed a system to effectively screen the STAT6 gene for targeting with small interfering (si) RNA molecules. By incorporating an in silico and in vitro screening system we were able to identify fourteen siRNA molecules suitable for pre-clinical drug development. Furthermore, we were able to demonstrate that modification of certain siRNAs, designed to improve in vivo longevity, was possible without significant loss of target knockdown efficacy and that the siRNA produced by our selection process did not induce demonstrable interferon responses. These data suggest that several STAT6-targeting siRNA suitable for pre-clinical development are available for potential use in the treatment of asthma.